Passed over for promotions: Women still severely underrepresented on financial sector boards - Elke Holst; Julia Schimeta (DIW Economic Bulletin, 2012)
Opportunities to increase the proportion of female board members in Germany's financial sector were missed during post-crisis period of management shakeups. As of 2011, the proportion of women on executive boards was still as low as in previous years: 3.2 percent in Germany's 100 largest banks and savings banks and 3.6 percent at 59 insurance companies surveyed. The percentage of women on supervisory boards is higher than on executive boards: women make up 16.6 percent of supervisory board members at banks and savings banks and 13.1 percent at insurance companies. At the banks, this represents an increase of 1.5 percentage points over 2006, or 0.14 percentage points per year. The higher proportion of women on supervisory boards is also the result of German codetermination law: 70.9 percent of the women on bank and savings bank supervisory boards and as much as 94.7 percent-that is, almost all-of the women on insurance sector supervisory boards were appointed to these positions as employees' representatives. Compared to the previous year, the proportion of female shareholder representatives declined again. The results also show that significant efforts are necessary in the public-sector if it is to act as a role model for the financial sector. Even in the top financial bodies of the EU and the German federal government, women are significantly underrepresented and therefore play little to no active role in key decisions affecting the financial market. When it comes to opening up corporate leadership positions to women, the financial sector has the advantage over other sectors that the majority of its employees are women. This should allow the sector to appoint more women and increase board diversity. By opening up corporate culture to women, the financial sector has an opportunity to set an example but also to get ahead of the curve on possible government regulations that could make this obligatory.
Keywords: G2; J16; J78; L32; M14; M51; 330; financial sector; board diversity; women CEOs; gender equality; management; public and private banks; insurance companies